Measurement of the charge asymmetry in semileptonic Bs0 decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We have performed the first direct measurement of the time-integrated flavor untagged charge asymmetry in semileptonic Bs0 decays ASLs,unt by comparing the decay rate of Bs0→μ+Ds-νX, where Ds- π- and →K+K-, with the charge-conjugate B̄s0 decay rate. This sample was selected from 1.3fb-1 of data collected by the D0 experiment in run II of the Fermilab Tevatron collider. We obtain ASLs,unt=[1.23±0.97(stat)±0. 17(syst)]×10-2. Assuming that Δms/Γ̄s 1, this result can be translated into a measurement of the CP-violating phase in Bs0 mixing: ΔΓs/Δmstan s=[2.45±1.93(stat)±0.35(syst)] ×10-2. © 2007 The American Physical Society.